Split appendix Mitrofanoffs have higher risk of complication than intact appendix or monti channels. Issue 5 (October 2021) - Zann, Anja; Sebastiao, Yuri; Ching, Christina C.; Fuchs, Molly; Jayanthi, Venakata R.; Wood, Richard J.; Levitt, Marc A.; DaJusta, Daniel
Summary: Introduction: Many patients with certain conditions require catheterizable channels for bladder and bowel management. There are a variety of accepted techniques for creating these channels; the split appendix technique enables the use of this organ for both procedures, obviating the need for more complex surgical procedures. Studies comparing outcomes across catheterizable channel types are limited. Objective: The aim of this study was to compare the urinary channel complication rates of the split appendix, intact appendix and transverse ileal tube (Monti) channels. We hypothesized that complication rates would be the same across all channel types. Study design: We retrospectively reviewed consecutive patients who underwent surgical creation of a urinary continent catheterizable channel. We recorded demographics, underlying diagnosis, body mass index, stoma location, surgical techniques, and surgical revisions. The primary outcome was complication (stenosis, leakage, or both) with or without surgical revision, and to compare the three different catheterizable channel types using time to event analysis. Results: From January 2014–July 2018, 107 patients underwent creation of a continent catheterizable urinary channel; 86 (80.4%) patients also underwent simultaneous procedure for antegrade bowel management. The mean age was 7 years; 66 (60.8%) were females. Intact appendices were used in 46 (43.0%), Monti channel in 25 (23.4%), and split appendix technique in 36 (33.6%). The corresponding complication rates with or without surgical revision was 21.7%, 36.0%, and 47.2%, respectively. The only independent factor associated with increased risk of complication was the split appendix technique; these channels were more than twice as likely to require surgical revision with an adjusted hazard ratio of 2.32 (Table 4). The majority of revisions in all groups were skin level (58.3%). The most common indication for surgical revision was stenosis (55.6%). Discussion: This analysis shows a statistically significant increase in risk of all complications, including an increase in need for surgical revision, in patients who underwent split appendix technique for simultaneous bladder and bowel catheterizable channels. This finding should be balanced with the fact that a bowel anastomosis is not required in cases where individuals need both a bowel and bladder catheterizable channel. This study is unique in its separation of split and intact appendix channels, and inclusion of patients experiencing complications that have not yet required surgical revision. Limitations of this study include its retrospective design, inclusion of a single institution, and the lack of consistency in documenting baseline appendiceal length. Conclusion: Split appendix catheterizable channels have a higher rate of channel complications than other techniques. The authors acknowledge that the split appendix technique has been proven feasible and effective, however recognize that it may not be appropriate for all patients and include counseling of the risks of its use. Summary Table Hazard Ratios (HR) for the risk of complications (with or without revision) over time. Summary Table Channel Type Unadjusted (Univariable) Adjusted (Multivariable) HR (95% CI) P HR (95% CI) P Intact Appendix 1 Reference 1 Reference Split Appendix 2.60 (1.19–5.70) 0.02 2.32 (1.04–5.19) 0.04 Monti 1.74 (0.70–4.29) 0.23 1.71 (0.69–4.22) 0.25